Discursos gráficos sobre la flexibilidad de la vivienda colectiva contemporánea - Folga, Alejandro (2018)
This paper presents a master's thesis whose main objective is to study the graphic representation of different ideas and concepts of flexibility, developed in a selection of contemporary collective housing projects. The concept of flexibility introduces temporality in the domestic project, therefore, the main object of study are the drawings in plan, because they are the ones that best express the uses of space and its possibilities for transformation. The research starts from the hypothesis that this graphics translate the ideas that underpin the projects and in this way become true graphic discourses.